Parental Acceptance of Children with Autistic Spectrum Disorder - Kaewkumfu, Papisa; Pontanya, Araya; Sriphetcharawut, Sarinya (Academic Psychiatry and Psychology Journal, 2018)
Abstract Objective: To understand the process of parental acceptance of children with Autism Spectrum Disorder (ASD) according to the 5 stages of grief and loss theory by Kubler Ross. Method: we used a qualitative phenomenological research design. Data were collected through in-depth interviews .In-depth data were collected by purposive sampling method for five informants from Tak association of parents of autistic child from May 2016 to October 2017. Result: The process of parental acceptance of a child with Autism includes the parent’s and the family’s denial about autism; a parent’s anger towards the inability to handle the child’s symptoms as well as towards the reaction of people surrounding the child; and guilty, negative thoughts about pregnancy and unsuitable parenting as being the cause of autism. Acceptance of autism leads to improvement in the child’s parenting and consequent treatment. A positive change in a parent’s attitude is the recognition that their child can make them see the good in bad. Conclusion: The process of parental acceptance of children with Autism Spectrum Disorder (ASD) is, in general, in accordance with the 5 stages of grief and loss theory by Kubler Ross. Keyword: Acceptance, Parent, Autism